Novel methods for analysis of radioactive samples using position-sensitive detectors, coincidence techniques and event-mode data acquisition - Turunen, Jani (2013)
A feasibility study on event-mode data acquisition systems, the alpha–gamma coincidence technique and position-sensitive detectors was conducted in Jyväskylä in the summer of 2007. Based on this study, a measurement device named PANDA (Particles And Non-Destructive Analysis) was designed and built at the Finnish Radiation and Nuclear Safety Authority (STUK). The PANDA device has two complementary measurement positions inside a vacuum chamber. The first measurement position hosts an HPGe detector for gamma and X-rays and a position-sensitive double-sided silicon strip detector (DSSSD) for alpha particles. The samples are analysed in close geometry between the detectors. The data are recorded in event mode and each event is time stamped. The second measurement position is equipped with a prototype silicon drift detector (SDD), which is used to detect conversion electrons and low-energy X-rays. The operation and performance of PANDA is presented via the measurements and analysis of various sample types. These include isolated radioactive particles, swipe samples, air filters and impactor samples. For example, the analysis of a cotton swipe sample containing 10 ng of Pu revealed that the 240Pu/239Pu atom ratio was 0.12 ± 0.03. The reference value given by the IAEA was 0.132. The results were congruent despite the fact that the sample itself was far from ideal. In another case, the alpha–gamma coincidence technique of PANDA was compared with traditional low-background gamma singles spectrometry. This comparison was realized by making long measurements in optimum geometries for a small radioactive particle. The analysis results proved that the alpha–gamma coincidence technique provide an approximately six times lower minimum detectable activity for 241Am.